Susceptibilidade de cepas de Candida albicans isoladas de secreção vaginal frente às micocinas de Wickerhamomyces anomalus - Rosseto, Lana Rubia Backes (2021)
Mycocins are substances that show a potential to affect sensitive fungi or bacteria. Wickerhamomyces anomalus is a mycocins producing yeast that has great biotechnological potential and is highly competitive in many habitats as it is adaptable to a wide range of growing conditions. Thus, they are targets of studies in different areas, including environment, industry and medical sciences. Candida albicans yeasts are of great importance because of the high frequency with which they colonize and infect the human host. And often, fungal infections are difficult to treat, a fact related to the acquisition by their etiologic agents of antifungal resistance. Due to this great resistance problem, new treatment alternatives are being studied. The objective of this work is to verify the inhibition of C. albicans isolated from vaginal secretion by W. anomalus. Tests were performed in solid medium and microdilution test, where the mycocins were efficient inhibiting the growth of C. albicans. Hemolysis and irritation tests in organotypic model, which showed that the mycocins produced by W. anomalus is safe and no irritating. Thus, the results of this work may provide scientific evidence for the application of mycocins in the production of new antifungal alternatives.